Comparative study on micronsized and nanosized carica papaya seed modified pullulan as biocoagulant in wastewater treatment - Deong, Jing Lie; Ahmad, Mazatusziha; Azhar, Nur Sabrina (Trans Tech Publications Ltd, Switzerland, 2021)
Plant-based coagulants have been used as an alternative material to replace chemical coagulant in wastewater treatment. So far, limited information was found on the incorporation of plant-based biocoagulant to natural polymers and the effect of particle size upon wastewater treatment application. Thus, this study was conducted to explore the effectiveness of micronsized and nanosized Carica Papaya (CP) seed modified pullulan as biocoagulant. Biocoagulant were prepared at different composition of CP to pullulan, with the CP content range from 1% to 9%. The biocoagulant were characterized via Particle Size Analyzer (PSA), Fourier Transform Infrared Spectroscopy (FTIR) and morphological analysis via Field Emission Scanning Electron Microscopy (FESEM). It was used to treat municipal wastewater. The treated wastewater quality was analyzed by jar test method with dosage of biocoagulant used was 0.6g/L. Result showed that the 10% (D10), 50% (D50) and 90% (D90) distribution of micronsized CP had particle size of 0.3675 μm, 0.8433 μm and 1.9537 μm respectively. The nanosized CP was 0.4473nm (D10), 2.3758nm (D50) and 2.9938nm (D90). Characterization of biocoagulant via FTIR revealed the appearance of O-H, C=O, C-H and C-O-C bond which contribute to particle interaction for turbidity reduction of wastewater. Jar test analysis found that at 3% micronsized CP and 7% nanosized CP were able to reduce turbidity up to 59.65% and 65.27% respectively. Both size of biocoagulant slightly changed the pH of treated wastewater to neutral, increased in dissolved oxygen (DO) and reduced in total suspended solid (TSS). Overall, nanosized CP was found more effective as compared to micronsized CP.